Empowering frontline providers to deliver universal primary healthcare using the Practical Approach to Care Kit. (24th October 2018) - Fairall, Lara; Cornick, Ruth; Bateman, Eric
Abstract : Lara Fairall and colleagues reflect on the successes and challenges of a programme to strengthen primary healthcare in low and middle income countries